PENGARUH MEDIA PEMBELAJARAN, FASILITAS DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SELAMA PANDEMI COVID-19 - Indah Dwi Setyorini; Siti Sri Wulandari (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This research is motivated by the condition of the Covid-19 pandemic which requires students to carry out learning with an online system which supported by learning media that provided by the teachers, sufficiently supportive facilities and a conducive learning environment so that learning outcomes of the students will increase. This research aims is to see the partial impact of the independent variable on the dependent variable. The subjects of this study were OTKP students of SMK IPIEMS in the Financial OTK subject. This research uses quantitative research with multiple linear regression analysis method. The sampling technique used in this research was the probability sampling with random sampling type, which was choose random sample without regarding the level. In this study, a sample was taken 53 students. The results obtained conclude that partially each independent variable has a significant effect on learning outcomes, that the result of t-test of learning media value 0.36 <0.05; learning facilities 0.22 <0.05 and learning environment 0.36 <0.05.